Cellular cannibalism in giant cells of central giant cell granuloma of jaw bones and giant cell tumors of long bones. Issue 2 (15th March 2016) - Sarode, Gargi S.; Sarode, Sachin C.; Gawande, Shailesh; Patil, Snehal; Anand, Rahul; Patil, Shankar Gouda; Patil, Prakash
Abstract: Aim: The aim of the present study was to investigate the relationship of central giant cell granuloma (CGCG) and giant cell tumor of long bones (GCT) with respect to cannibalistic giant cells (GCs). Method: Sixteen cases each of CGCG and GCT were histopathologically analyzed for cannibalistic GCs. One hundred GCs were examined in each section, and the number of cannibalistic GCs was expressed in percentage. Results: Cannibalistic GCs were seen in all cases of CGCG and GCT (100%). GCT showed significantly higher mean cannibalistic GC frequency (44.81 ± 1.013) than CGCG (32.06 ± 1.398), aggressive CGCG (38.17 ± 1.579), non‐aggressive CGCG (28.40 ± 0.6360), non‐recurrent CGCG (30.42 ± 1.417), and recurrent CGCG (37.00 ± 2.483). In aggressive CGCG, the mean cannibalistic GC frequency was significantly higher (38.17 ± 1.579) than the non‐aggressive variant (28.40 ± 0.6360). Recurrent CGCG cases showed significantly higher mean cannibalistic GC frequency (37.00 ± 2.483) than non‐recurrent cases (30.42 ± 1.417). Similarly, recurrent GCT showed significantly higher mean cannibalistic GC frequency (47.4 ± 4.97) than non‐recurrent GCT (43.63 ± 3.1). Conclusion: The distinctness of CGCG and GCT was observed in terms of mean cannibalistic GC count. The assessment of cannibalistic GC in CGCG and GCT could help in predicting the biological behavior and grading of the tumor.